Tumor necrosis factor alpha sensitizes spinal cord TRPV1 receptors to the endogenous agonist N-oleoyldopamine - Spicarova, Diana; Palecek, Jiri (Journal of neuroinflammation, 2010)
Modulation of synaptic transmission in the spinal cord dorsal horn is thought to be involved in the development and maintenance of different pathological pain states. The proinflamatory cytokine, tumor necrosis factor alpha (TNFalpha), is an established pain modulator in both the peripheral and the central nervous system. Up-regulation of TNFalpha and its receptors (TNFR) in dorsal root ganglion (DRG) cells and in the spinal cord has been shown to play an important role in neuropathic and inflammatory pain conditions. Transient receptor potential vanilloid 1 (TRPV1) receptors are known as molecular integrators of nociceptive stimuli in the periphery, but their role on the spinal endings of nociceptive DRG neurons is unclear. The endogenous TRPV1 receptor agonist N-oleoyldopamine (OLDA) was shown previously to activate spinal TRPV1 receptors. In our experiments the possible influence of TNFalpha on presynaptic spinal cord TRPV1 receptor function was investigated. Using the patch-clamp technique, miniature excitatory postsynaptic currents (mEPSCs) were recorded in superficial dorsal horn neurons in acute slices after incubation with 60 nM TNFalpha. A population of dorsal horn neurons with capsaicin sensitive primary afferent input recorded after the TNFalpha pretreatment had a basal mEPSC frequency of 1.35 +/- 0.20 Hz (n = 13), which was significantly higher when compared to a similar population of neurons in control slices (0.76 +/- 0.08 Hz; n = 53; P < 0.01). In control slices application of a low concentration of OLDA (0.2 uM) did not evoke any change in mEPSC frequency. After incubation with TNFalpha, OLDA (0.2 uM) application to slices induced a significant increase in mEPSC frequency (155.5 +/- 17.5%; P < 0.001; n = 10). Our results indicate that TNFalpha may have a significant impact on nociceptive signaling at the spinal cord level that could be mediated by increased responsiveness of presynaptic TRPV1 receptors to endogenous agonists. This could be of major importance, especially during pathological conditions, when increased levels of TNFalpha and TNFR are present in the spinal cord.
Keywords: miniaturní postsynaptické potenciály; Synaptic Transmission; TRPV Cation Channels; Patch-Clamp Techniques; Analysis of Variance; Male; Rats, Wistar; Tumor Necrosis Factor-alpha; Spinal Cord; excitační postsynaptické potenciály; mužské pohlaví; metoda terčíkového zámku; potkani Wistar; dopamin; nervový přenos; krysa rodu Rattus; Dopamine; Animals; mícha; analýza rozptylu; Miniature Postsynaptic Potentials; zvířata; buňky zadních rohů míšních; Rats; TNF-alfa; Posterior Horn Cells; kationtové kanály TRPV; Excitatory Postsynaptic Potentials